2015
DOI: 10.1111/iju.12700
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of aberrantly expressed microRNAs in prostate cancer

Abstract: microRNAs, a class of small non-coding RNAs, regulate protein-coding gene expression by repressing translation or cleaving RNA transcripts in a sequence-specific manner. A growing body of evidence suggests that microRNAs contribute to prostate cancer development, progression and metastasis. Based on reports describing microRNA expression signatures, several differentially expressed microRNAs have been discovered. In the present review, eight genome-wide microRNA expression signatures were used to select aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 124 publications
(296 reference statements)
0
89
1
1
Order By: Relevance
“…133,134 Cancer stem cell-related miRNA Recent studies have suggested that miRNA contribute to tumor initiation by regulating the properties of CSC, including their selfrenewal, de-differentiation and drug resistance. 5,9,135 Han et al 136 demonstrated that the formation of CSC-like cells that were undergoing EMT was associated with the overexpression of hypoxiainducible factor 1α and that this process was regulated by miR-21. Let-7 has an important role to regulate the function of CSC, because the reduction of let-7 expression inhibits differentiation and maintains proliferation.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…133,134 Cancer stem cell-related miRNA Recent studies have suggested that miRNA contribute to tumor initiation by regulating the properties of CSC, including their selfrenewal, de-differentiation and drug resistance. 5,9,135 Han et al 136 demonstrated that the formation of CSC-like cells that were undergoing EMT was associated with the overexpression of hypoxiainducible factor 1α and that this process was regulated by miR-21. Let-7 has an important role to regulate the function of CSC, because the reduction of let-7 expression inhibits differentiation and maintains proliferation.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…1 On the other hand, microRNAs (miRNAs) are small (19-22 bases in length) non-coding RNAs, and negatively regulate protein-coding gene expressions by promotion of mRNA degradation or inhibition of translation. 5 In breast cancer, various miRNAs have been shown to be deleted or to exhibit downregulated or upregulated expression. Recently, it has been demonstrated that aberrational miRNAs targeting to several cancer-related genes induce cancer initiation, progression, metastasis or drug resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that >30% of human genes are regulated by miRNAs, and that they are involved in a variety of biological functions, including proliferation, differentiation, cell cycle, apoptosis, angiogenesis, invasion and metastasis (13,14). An accumulating number of studies have reported that miRNA expression levels are dysregulated in a variety of human cancer types (15)(16)(17). miRNAs play key functions in the initiation and progression of tumors by serving as oncogenes or tumor suppressors, primarily depending on the roles of their target genes (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, downregulated antitumor miRNAs can lead to overexpression or activation of oncogenes. Discovery of microRNA (miRNA)-regulated genes improves our understanding RNA networks in cancer cells [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%